Validitas Media Pembelajaran Multimedia Interaktif Terintegrasi Deep Learning Mata Pelajaran IPA untuk Meningkatkan Literasi Sains - Rohmah, Khafidhotur; Murtini, Iin (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
The advancement of science and technology encourages the integration of technology in education, especially in science education. This study aims to develop Interactive Multimedia and Deep Learning-Based Science Learning Media to improve scientific literacy, while testing the validity of learning media products. This study uses an R&D approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), which only reaches the development stage. Data were collected through validation sheets assessed by 3 expert validators. The data analysis technique in this study used quantitative analysis. The results of the validity test showed an average of: Material (86%), Systematics (89.3%), Language (88.3%), and Graphics (90.5%). The overall average score of 88.5% with this product category is very valid. Based on these results, it is stated that the validity test of the Validity of Interactive Multimedia Learning Media Integrated Deep Learning for Science Subjects to Improve Scientific Literacy is stated to be very valid, therefore further research is needed on the effectiveness and practicality test so that the product can be used in learning.